2017
DOI: 10.1002/acn3.441
|View full text |Cite
|
Sign up to set email alerts
|

Sex matters: repetitive mild traumatic brain injury in adolescent rats

Abstract: ObjectiveWhether sex differences contribute to the heterogeneity of mild traumatic brain injury (mTBI) and repeated mTBI (RmTBI) outcomes in adolescents is unknown. Therefore, this study examined changes in, and differences between, male and female rats following single mTBI and RmTBI.MethodsRats were given a single mTBI, RmTBI (i.e., 3x), or sham injuries. Injuries were administered using a lateral impact model that mimics forces common in human mTBI. After the final injury, rats underwent extensive behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
93
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 73 publications
10
93
3
Order By: Relevance
“…Using only male animals disregards the diverse response in outcome of mTBI in males and females (Gallagher et al, ). In the reviewed studies comparing sex differences in mTBI, differences were seen in male and female prefrontal cortex atrophy; white matter integrity in the corpus callosum; microglial activation; brain mRNA expression of GFAP, MBP, and tau; short‐term working memory; depressive‐like behavior; and social interaction (Hehar, Yu, Ma, & Mychasiuk, ; Mychasiuk, Hehar, et al, ; Wright, O'Brien, Shultz, & Mychasiuk, ; Yamakawa, Lengkeek, et al, ). While the majority of human CTE cases in the literature are male (McKee et al, ), it is unlikely that this represents the true proportion of CTE cases, but instead indicates that current research has been undertaken in traditionally male domains in sports, such as football and boxing, and occupations such as military service.…”
Section: Discussionmentioning
confidence: 99%
“…Using only male animals disregards the diverse response in outcome of mTBI in males and females (Gallagher et al, ). In the reviewed studies comparing sex differences in mTBI, differences were seen in male and female prefrontal cortex atrophy; white matter integrity in the corpus callosum; microglial activation; brain mRNA expression of GFAP, MBP, and tau; short‐term working memory; depressive‐like behavior; and social interaction (Hehar, Yu, Ma, & Mychasiuk, ; Mychasiuk, Hehar, et al, ; Wright, O'Brien, Shultz, & Mychasiuk, ; Yamakawa, Lengkeek, et al, ). While the majority of human CTE cases in the literature are male (McKee et al, ), it is unlikely that this represents the true proportion of CTE cases, but instead indicates that current research has been undertaken in traditionally male domains in sports, such as football and boxing, and occupations such as military service.…”
Section: Discussionmentioning
confidence: 99%
“…TWI measures have previously been shown to be altered in preclinical mTBI23, 24 and repeated mTBI25 models that involved the use of anesthetic and/or craniotomy. Compared to the sham group, repeated ACHI resulted in a significant increase in track density (i.e., TDI) in both the ipsilateral and contralateral fimbria, as well as the contralateral external capsule at Day 1.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is the most commonly applied DWI method, and initial studies have reported changes on DTI measures (e.g., fractional anisotropy, FA) in the clinical mTBI setting. [19][20][21][22] Furthermore, new DWI acquisition and analysis methods (e.g., track-weighted imaging, TWI) are being developed that may also be sensitive to mTBIs, [23][24][25] but remain to be comprehensively studied in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of increased FA and decreased RD in our study is in agreement with many of the reported clinical outcomes of pediatric mTBI, albeit many of the existing studies examined various WM structures in much shorter time frame [65-68]. Interestingly, a recent study examining rmTBI in adolescent rats showed reductions in ADC and AD but no significant alterations in FA or RD 2 weeks after the final injury in the CC, although these differences could be attributed to a different injury model (3 repeated injuries 4 days apart) or the age at injury (P30) [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Another preclinical pediatric rmTBI study reported early evidence of axonal injury and microglial activation, as well as long-term associative learning deficits after 3 weeks and 3 months, respectively [20]. Furthermore, motor deficits, anxiety-like behaviors, and WM deficits have been reported in adolescent rmTBI using a rodent model [21]. However, the long-term pathophysiology and associated injury mechanisms, especially in the WM, have not been well characterized in the developing brain.…”
Section: Introductionmentioning
confidence: 99%